Analysis of Structuralism and Religious Values in the Short Story Pengemis dan Shalawat Badar in the Anthology Short Story of Senyum Karyamin by Ahmad Tohari - Wasniah Wasniah; Yulianeta Yulianeta (Journal of General Education and Humanities, 2022)
This study aims to determine structuralism and religious values in the short story "Pengemis dan Shalawat Badar". Know the elements in the short story. In the research entitled: Analysis of Structuralism and Religious Values in the Short Story Pengemis dan Shalawat Badar in the Anthology Short Story of Senyum Karyamin by Ahmad Tohari. The researcher uses a method that refers to qualitative research and uses data analysis techniques where the researcher is the key instrument. The data collection technique combines inductive data analysis, description and conclusion. The study's results emphasized meaning rather than generalizations, found religious themes, and explained many values of life that could take in the short story.